Size-dependent structure and magnetic properties of co-evaporated Fe-SiO2 nanoparticle composite film under high magnetic field - Yonghui Ma; Guojian Li; Jiaojiao Du; Mengmeng Li; Jianhao Wang; Qiang Wang (AIP Advances, 2016)
Composite film of Fe nanoparticles embedded in a SiO2 matrix has been prepared by the co-evaporation of Fe and SiO2. Both source temperature and in-situ high magnetic field (HMF) have been used to adjust the Fe particle size and the growth of Fe-SiO2 film. The size of Fe particle decreased with increasing the source temperature without HMF. When HMF was presented during the growth of the film, the size of Fe particle was enlarged and reduced for source temperatures of 1300 °C and 1400 °C, respectively. Meanwhile, the preferred orientation of the film grown at 1400 °C became uniform with the application of HMF. In addition, it is also found that the film was formed in two layers. One layer is formed by the Fe particle, while the other is free of Fe particles due to the existence of more SiO2. The structural variation has a significant effect on the magnetic properties. The coercivity (90 Oe) of the 1300 °C film is much higher than that (6 Oe) of the 1400 °C film with a small particle size and uniform orientation. The saturation magnetization can be increased by increasing the Fe particle volume fraction. This study develops a new method to tune the soft magnetic properties by the co-evaporation of Fe and SiO2.